Kejahatan Transnasional Terhadap Peredaran Narkoba Internasional Ditinjau Dari Kasus Fredy Pratama - Nanda Aulia Mardika; Daud Sofyan Timur Siahaan; Vavella Chryzalmantia; Yarra Raja Seraf; Herly Antoni (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2023)
This research examines the problem of transnational crime in international drug trafficking from the case of Fredy Pratama, who is an Indonesian youth who was arrested in 2021 for trying to smuggle 1.2 kilograms of cocaine to Australia. His case highlights the challenges law enforcement faces in combating transnational drug trafficking, as well as the devastating impact these crimes have on the Nation. The aim of this research is to explore in more detail the Fredy Pratama case and find out the impact of his crime. Legal documents for this research were obtained from a literature review. This research uses a qualitative descriptive analysis method. From the research results, it was concluded that the Fredy Pratama case was a microcosm of a larger problem, namely transnational drug trafficking. Disclosure of this case is also the greatest salvation for the lives of the nation's children from the threat of drugs. The suspects were charged with multiple articles, namely TPPU and Law of the Republic of Indonesia Number 35 of 2009 concerning Narcotics and Article 114 paragraph (2) in conjunction with Article 132 paragraph (2) subsidiary Article 112 paragraph (2) in conjunction with Article 132 paragraph (2), with threats death penalty or life imprisonment.